2020
DOI: 10.1186/s12870-020-02523-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of red and blue light on leaf anatomy, CO2 assimilation and the photosynthetic electron transport capacity of sweet pepper (Capsicum annuum L.) seedlings

Abstract: Background: The red (R) and blue (B) light wavelengths are known to influence many plant physiological processes during growth and development, particularly photosynthesis. To understand how R and B light influences plant photomorphogenesis and photosynthesis, we investigated changes in leaf anatomy, chlorophyll fluorescence and photosynthetic parameters, and ribulose-1, 5-bisphosphate carboxylase/oxygenase (Rubisco) and Calvin cyclerelated enzymes expression and their activities in sweet pepper (Capsicum annu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 81 publications
3
27
0
Order By: Relevance
“…This increased carbohydrate accumulation has been associated with both down-regulation of photosynthesis [ 62 ] and feedback inhibition on sucrose synthesis and sugar phosphates’ cytosol accumulation [ 63 ]. Since B light generally up-regulates the genes encoding key enzymes in the Calvin-Benson cycle, feedback control is ruled out in the inhibition of photosynthesis under monochromatic B light [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…This increased carbohydrate accumulation has been associated with both down-regulation of photosynthesis [ 62 ] and feedback inhibition on sucrose synthesis and sugar phosphates’ cytosol accumulation [ 63 ]. Since B light generally up-regulates the genes encoding key enzymes in the Calvin-Benson cycle, feedback control is ruled out in the inhibition of photosynthesis under monochromatic B light [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The enriched GO terms of the DEGs in Group 3 indicated that the expression of the genes that were involved in the photosynthesis and electron transport under blue light was higher than that under red light ( Table 1 ). It has been shown that CO 2 assimilation, photosystem II (PSII) electron transportation, and photosynthesis in plants treated with red light were impaired to a greater extent than the plants treated with blue light [ 42 , 43 ]. Ribose-1, 5-bisphosphate carboxylase/oxygenase (Rubisco) activity under red light was also lower than that under blue light [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that CO 2 assimilation, photosystem II (PSII) electron transportation, and photosynthesis in plants treated with red light were impaired to a greater extent than the plants treated with blue light [ 42 , 43 ]. Ribose-1, 5-bisphosphate carboxylase/oxygenase (Rubisco) activity under red light was also lower than that under blue light [ 43 ]. In this study, the expression of gene encoding Rubisco small subunit under blue light was higher than that red light ( Fig 2B and S4 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Artificial irradiation influences the carotenoid content in leaves and fruits [ 23 , 26 ]. As reported by Li et al [ 27 ], mixed R and B light alters plant photomorphogenesis and photosynthesis, mainly by affecting the leaf anatomy, stoichiometry of photosystems I and II, photosynthetic electron transport, and the expression and activity of key Calvin cycle enzymes. It was found that when pepper seedlings were illuminated with mixed RB (red–blue) light, the leaves were thicker and the photosynthetic electron transport efficiency and photosynthetic rate increased compared to plants illuminated with white light; therefore, using LED lamps with a higher proportion of blue light can increase the supplementary light efficiency.…”
Section: Introductionmentioning
confidence: 97%